Distribution of Artificial Radionuclides in Abandoned Cattle in the Evacuation Zone of the Fukushima Daiichi Nuclear Power Plant - Fukuda, Tomokazu (Public Library of Science, 2013)
The Fukushima Daiichi Nuclear Power Plant (FNPP) accident released large amounts of radioactive substances into the environment. In order to provide basic information for biokinetics of radionuclides and for dose assessment of internal exposure brought by the FNPP accident, we determined the activity concentration of radionuclides in the organs of 79 cattle within a 20-km radius around the FNPP. In all the specimens examined, deposition of Cesium-134 ((134)Cs, half-life: 2.065 y) and (137)Cs (30.07 y) was observed. Furthermore, organ-specific deposition of radionuclides with relatively short half-lives was detected, such as silver-110m ((110m)Ag, 249.8 d) in the liver and tellurium-129m ((129m)Te, 33.6 d) in the kidney. Regression analysis showed a linear correlation between the radiocesium activity concentration in whole peripheral blood (PB) and that in each organ. The resulting slopes were organ dependent with the maximum value of 21.3 being obtained for skeletal muscles (R(2) = 0.83, standard error (SE) = 0.76). Thus, the activity concentration of (134) Cs and (137)Cs in an organ can be estimated from that in PB. The level of radioactive cesium in the organs of fetus and infants were 1.19-fold (R(2) = 0.62, SE = 0.12), and 1.51-fold (R(2) = 0.70, SE = 0.09) higher than that of the corresponding maternal organ, respectively. Furthermore, radiocesium activity concentration in organs was found to be dependent on the feeding conditions and the geographic location of the cattle. This study is the first to reveal the detailed systemic distribution of radionuclides in cattle attributed to the FNPP accident.